2020
DOI: 10.1155/2020/8834299
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Poststroke Depression in Ischemic Stroke Patients in Ethiopia

Abstract: Background. There is limited information and research carried out regarding the prevalence of poststroke depression (PSD) in the study area. Psychiatric disorders complicate a significant proportion of patients suffering from stroke. This of course have a great negative impact on our knowledge about poststroke depression in Ethiopia, and poststroke depression complicates a significant number of stroke patients and their rehabilitation. Methods. A cross-sectional study on all patients aged above 18 years and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…The prevalence of post stroke depression found in the current study is comparable with the results of the studies done in Iran 45% [ 25 ], 47.4% [ 26 ], another systematic review and meta-analysis study of Iran 46.9% [ 27 ] and Finland 48.1% [ 28 ]. However, the reported prevalence of PSD in our study was found to be higher than the studies done in USA 31% [ 29 ], German 31.1 [ 30 ], New Zealand 23% [ 31 ], Ghanaians studies 36.5% [ 32 ], Uganda 31.5% [ 33 ], Nigeria 25.5 [ 34 ], Addis Ababa, Ethiopia 32.2% [ 22 ]. This discrepancy could be attributable to the difference in the study populations in terms of types of strokes, the tool used for screening depression or other socio-demographic variations and severity of depression considered.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The prevalence of post stroke depression found in the current study is comparable with the results of the studies done in Iran 45% [ 25 ], 47.4% [ 26 ], another systematic review and meta-analysis study of Iran 46.9% [ 27 ] and Finland 48.1% [ 28 ]. However, the reported prevalence of PSD in our study was found to be higher than the studies done in USA 31% [ 29 ], German 31.1 [ 30 ], New Zealand 23% [ 31 ], Ghanaians studies 36.5% [ 32 ], Uganda 31.5% [ 33 ], Nigeria 25.5 [ 34 ], Addis Ababa, Ethiopia 32.2% [ 22 ]. This discrepancy could be attributable to the difference in the study populations in terms of types of strokes, the tool used for screening depression or other socio-demographic variations and severity of depression considered.…”
Section: Discussioncontrasting
confidence: 83%
“…The samples were obtained from a relatively small population (N = 180). The following assumptions were used to determine the required sample: prevalence of post stroke depression is 32.2% taken from the previous study [ 22 ], a confidence level of 95%, 5% margin of error., the required sample size was obtained by the following calculation n = (za/2) 2 p (1-p)/d 2 , where n = sample size. Z = 95% confidence limit (1.96) p = proportion of the post stroke depression which take prevalence of 32.2% d = margin of error or degree of accuracy desired (0.05) n= (1.96) 2 x (0.322) (0.678)/(0.05) 2 = 336.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of stroke-related factors, ischemic stroke type was found statistically associated with depression and anxiety, and also significant relation was observed between lesion location of stroke (left side) and depression or anxiety corresponding to the study conducted by Tsehayneh and Tafesse [14] and Leppävuori et al [15].…”
Section: Discussionsupporting
confidence: 66%
“…The care burden is the physical, psychological, and social disruption related to the negative caring experience that was divided into objective and subjective components [10] . Studies have reported that 68.4% of the caregivers in China had a moderate burden and above [11] , rates that are higher than those reported among stroke patients [12,13] . Previous research has shown that care burden in caregivers of stroke patients will increase over time [14] and even contribute to depression if the proper intervention is not provided [11] .…”
Section: Introductionmentioning
confidence: 80%